[2+2] Halogen-bonded boxes employing azobenzenes. Issue 60 (14th May 2019) - Nieland, Esther; Topornicki, Thomas; Kunde, Tom; Schmidt, Bernd M.
Abstract : Herein, we report the synthesis and crystal structures of three [2+2] supramolecular boxes assembled by halogen bonding. Abstract : Herein, we report the synthesis and crystal structures of three [2+2] supramolecular boxes assembled by halogen bonding. The discrete, two-dimensional boxes with a length of 25–30 Å are based on rigid u-shaped halogen acceptors paired with highly fluorinated, azobenzenes bearing halogen bond donors.